Performance Evaluation of Merauke Archipelago Fisheries Port: GAP Analysis, Challenges, and Opportunities for Strengthening Port Services - Chalvyn Silasa Pakidi; Bonny Lantang (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Purpose of the Study, this study aims to assess the performance of the Merauke Archipelago Fisheries Port (PPN) using national standard indicators and to identify gaps (GAPs) across key components including administration, facilities, public services, investment, and industry. The research seeks to map priority areas that require strategic improvements to strengthen port competitiveness and support sustainable fisheries development in South Papua. Materials and Methods, A descriptive-evaluative design was employed by comparing actual port performance with national standards. The analysis involved evaluative scoring, GAP analysis to identify discrepancies between expected and actual conditions, and descriptive interpretation for deeper explanation of performance strengths and weaknesses. Results, the evaluation shows that Merauke PPN achieves a good performance level with a total score of 73.75 out of 100. Strong performance is recorded in physical and operational facilities such as pond capacity, pier dimensions, production volume, and vessel visit frequency. However, critical GAPs are found in digitalization (SHTI and SISKA systems), limited technical facilities for docking and repair, low logistics service efficiency, minimal processing industry presence, and insufficient human resources. Conclusions, the port’s strengths remain concentrated in physical infrastructure, while functional and managerial components lag behind. Four key improvement strategies are recommended: modernizing information systems, providing technical support facilities, developing the processing industry, and strengthening human resource capacity to enhance competitiveness and sustainability.